Analisis Pelaksanaan SIMRS pada Unit Kerja Rekam Medis dengan Metode Technology Acceptance Model (TAM) - Deni Maisa Putra; Chairunnisa Mufli Hunna; Washi Fadhila (Jurnal Rekam Medis dan Informasi Kesehatan, 2022)
Hospital Management Information System (SIMRS) is an application system used in the management of hospital services aimed at improving health services. The success of an information system depends on how users are willing to accept and use it to achieve organizational goals. The purpose of this study was to find out how the SIMRS was implemented in the medical record work unit with the TAM method. The method used in this study is a literature study to examine journals regarding the implementation of SIMRS in the medical record work unit with the tam method, the data collection used is using secondary data and analyzed descriptively by describing the existing facts, data analysis was carried out by looking for similarities, dissimilarities, views, summaries of several studies. The results of the 12 literature study journals show that in terms of the SIMRS components, they are not adequate and sufficient in providing services. The acceptance of the system by the user from the aspect of usefulness and the aspect of ease of knowing that the information system is already useful for users and easy to operate. The acceptance of the system from the attitude of the user is quite satisfied with the existence of the information system. Acceptance of information systems from the user's behavioral intentions assume good and have a desire to motivate other users. In addition, the acceptance of information systems depends on the real conditions of users where the information system increases their productivity which is reflected in the real conditions of use. To maintain user acceptance of the information system, it is hoped that the hospital will conduct regular training to improve user skills in order to avoid errors that can arise in the future and the hospital must meet the information system components to support the implementation of SIMRS